FATCA: The Outclawing Laws That Compels Local International Financial Institutions in Banking Compliance - Hakimah Yaacob; Nur Nazirah Norni; Muhammad Iqmal Hisham Kamaruddin (USIM Press, 2024)
Readings in Sustaining Global Halal Ecosystem : (Collection of Articles from The 2nd International Halal Management Conference)